2014
DOI: 10.1039/c4cc07353c
|View full text |Cite
|
Sign up to set email alerts
|

Extendable nickel complex tapes that reach NIR absorptions

Abstract: Stepwise synthesis of linear nickel complex oligomer tapes with no need for solid-phase support has been achieved. The control of the length in flat arrays allows a fine-tuning of the absorption properties from the UV to the NIR region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Quinoidal precursors 2 (Bandrowski base) 41 and 3 42 were reacted with the aldehyde 4previously unknown -in EtOH in the presence of piperidine to afford the expected benzobis(imidazoles) 5 and 6, respectively, in 46 and 49 % yields (Scheme 1). In situ deprotection -using TBAF (tetra-n-butylammonium fluoride) -gave target compounds A and B, which could be readily reacted in the presence of gold either as molecular junction, or as unit able to form self-assembled monolayers, because of the presence of terminal -SH thiol functions.…”
Section: Synthesis Of the Molecular Switch A And B And Characterizatimentioning
confidence: 99%
“…Quinoidal precursors 2 (Bandrowski base) 41 and 3 42 were reacted with the aldehyde 4previously unknown -in EtOH in the presence of piperidine to afford the expected benzobis(imidazoles) 5 and 6, respectively, in 46 and 49 % yields (Scheme 1). In situ deprotection -using TBAF (tetra-n-butylammonium fluoride) -gave target compounds A and B, which could be readily reacted in the presence of gold either as molecular junction, or as unit able to form self-assembled monolayers, because of the presence of terminal -SH thiol functions.…”
Section: Synthesis Of the Molecular Switch A And B And Characterizatimentioning
confidence: 99%
“…9- 18 We also highlighted that the unsubstituted parent 3 behaves differently from 1 in coordination chemistry owing to the absence of N-substituents that allows the formation of polynuclear complexes with controlled lengths. 19 These observations suggest the study of QDIs 2 that can be viewed as the hybrid form of 1 and 3.…”
Section: Introductionmentioning
confidence: 97%
“…In this strategy,t he ligand design is crucial since maximizing the conjugation through coordination requires keeping the p-d systems as coplanar as possible.Previous studies reported that low-lying p*o rbitals of quinoidal ligands can mix extensively with the valence d-orbitals of am etal center, yielding complexes in which the electrons could be delocalized over both the metal and the ligand. [15][16][17] In this context, derivatives of 2,5-diamino-1,4-benzoquinonediimines (2HQDI) are particularly appealing because of their fascinating optical properties, [18,19] and remarkable ability to serve as ligand in coordination chemistry.U nlike the N-substituted systems (N-alkyl or N-aryl), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] the coordination chemistry of the parent (i.e.u nsubstituted) molecule 2HQDI in solution has been poorly investigated probably due to its low solubility and specific reactivity that induced unwanted side-reactions. [35] Some of us showed that the absence of N-substituents (no steric hindrance) allows au nique behavior resulting from the stepwise formation of coplanar polynuclear complexes NiQDI with up to 3r epeat units (n 3) ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%